Towards a consistent modelling of plasma edge turbulence in mean field transport codes: Focus on sputtering and plasma fluctuations. (August 2017) - Marandet, Y.; Bufferand, H.; Nace, N.; Valentinuzzi, M.; Ciraolo, G.; Tamain, P.; Bucalossi, J.; Galassi, D.; Ghendrih, Ph.; Mellet, N.; Serre, E.
Highlights: In addition to closures needed in transport codes for turbulent fluxes, there are issues related to non-linear source/sinks. Accounting for fluctuations increase sputtering in the sub-threshold energy range, though thermal dispersion smoothen threshold effects. "Fluctuation dressed" sputtering coefficients are introduced, and a first attempt at parametrizing the latter with mean fields is presented. Such a parametrization requires a model calculating the fluctuation levels from mean fields. Abstract: Transport codes are the main workhorses for global edge studies and modern divertor design. These tools do not resolve turbulent fluctuations responsible for the bulk of cross-field transport in the Scrape-off Layer (SOL), and solve mean field equations instead. Turbulent fluxes are modelled by diffusive transport along the gradients of the mean fields. Improvements of this description, on the basis of approaches developed in computational fluid dynamics are discussed, broadening the outlook given in Bufferand et al. (2016) [10]. This contribution focuses on additional closure issues related to non-linearities in sources/sinks from plasma-wall interactions, here sputtered fluxes from the plasma facing components. "Fluctuation dressed" sputtering yields Yeff are introduced and calculated from turbulence simulations. Properly taking fluctuations into account is shown to lead to higher sputtering at sub-threshold energies compared to mean field predictions. As a first step towards an implementation in a transport code, the possibility of parametrizing Yeff in terms of the mean fields is tentatively investigated.